2000
DOI: 10.1016/s0042-6989(00)00008-0
|View full text |Cite
|
Sign up to set email alerts
|

A new test of contour integration deficits in patients with a history of disrupted binocular experience during visual development

Abstract: Previous studies have suggested that the integration of orientation information across space is impaired in amblyopia. We developed a method for quantifying orientation-domain processing using a test format that is suitable for clinical application. The test comprises a graded series of cards where each card includes a closed path (contour) of high contrast Gabor signals embedded in a random background of Gabor signals. Contour visibility in both normals and patients with histories of abnormal binocular vision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
92
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 25 publications
7
92
0
4
Order By: Relevance
“…also performed well on the present task, Figure 13. Examples of displays used in the experiments presented in Kovács et al (2000) of contours made of local Gabor units. A: Easy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…also performed well on the present task, Figure 13. Examples of displays used in the experiments presented in Kovács et al (2000) of contours made of local Gabor units. A: Easy.…”
Section: Resultsmentioning
confidence: 99%
“…and R.N. participated in this study, and we used the data from the neurologically intact participants reported in Kovács et al (2000) against which to compare their thresholds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…McKee et al, 2003!. Recent work has shown a much broader range of deficits in amblyopes that are not easily explained by or correlated with the basic loss in spatial vision. For example, contour integration and other tasks that require spatial integration are impaired in amblyopia~Hess et al, 1997; Hess & Demanins,1998;Kovács et al, 2000;Mussap & Levi, 2000;Chandna et al, 2001;Kozma & Kiorpes, 2003!. Such "high-level Although low-level orientation discrimination is largely found to be normal in amblyopes~e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1-4), including reductions in visual acuity (VA), contrast-sensitivity function (CSF), and vernier acuity as well as spatial distortion (5), abnormal spatial interactions (6, 7), and impaired contour detection (8,9). In addition, amblyopic individuals suffer from binocular abnormalities such as impaired stereoacuity and abnormal binocular summation.…”
mentioning
confidence: 99%